Pengaruh Pendekatan Pensyarah Terhadap Sikap Dan Gaya Pembelajaran Pelajar Dalam Matematik Kejuruteraan Satu - Hasanah Safein @ Shafie; Anisah Jawawi; Mohamad Shafie Isa (Politeknik & Kolej Komuniti Journal of Social Sciences and Humanities, 2017)
This study was carried out to identify the influence of lecturers approach related with attitudes and learning styles on Mathematics Engineering 1 Course at Kota Bharu Polytechnic. A total of 443 students were selected as respondents to identify the influence of lecturers approach that influenced the attitude and style of student learning in the Mathematics Engineering 1 Course. Questionnaires were used to collect the data and analyzed using the Statistical Package for Social Sciences (SPSS) 20.0 by using T-Test and Annova. The results showed that respondents had positive attitudes while studying Engineering Mathematics 1 at Polytechnic. The study also found that the interest, role of lecturers and teaching approaches can influence the student learning styles in Engineering Mathematics 1. The overall findings also show that students have a positive thinking about the attitudes and learning styles of lecturers approach and syllabus of Engineering Mathematics 1 Courses.